„Geniusz jutra na atomy rozbity”. O epokowych diagnozach Piotra Chmielowskiego i Antoniego Langego - Jauksz, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The article presents an unofficial discussion that took place between one of the most prominent Polish critics of the late 19th century and Antoni Lange, a raising poet of the 90s, whose work had gained little attention from the older colleague. Mentioned briefly in Chmielowski’s Współczesni poeci polscy in 1895, Lange responded to some of the critic’s fterwards. Chmielowski did not respond to that directly, however, his review of Lange’s volume of poetry published at the time and the will to defend his claims using the adversary’s poetry as a pretext shows that the young poet had succeeded in provoking the respected critic to take defensive position. The two writers, discussing an ongoing ‘crisis’ of poetry, present their own perspectives on the roots of the situation. Chmielowski’s claims from the beginning of the 20th century prove that the dispute, unofficial as it was, was won by Antoni Lange.